Telehealth in behavioral intervention with mothers of children with autism (Brazilian Journal of Behavioral and Cognitive Therapy, 2024)
The present work aimed to describe the functioning of a behavioral intervention in the telehealth format, conducted by undergraduate and postgraduate students from the Psychology course at a public university in the interior of São Paulo, together with seven families of children with autism. . The procedure consisted of synchronous and asynchronous guidance with families, mediated by technological resources to apply teaching programs with their children. The number of programs applied by mothers, the number of interactions between mothers and students and the satisfaction of mothers participating in the proposal were measured. 248 teaching programs were applied in five areas of child development (cognition, motor area, language, socialization and self-care), approximately 180 synchronous interactions and 857 asynchronous interactions between mothers and interns or tutors were carried out, and mothers' satisfaction averaged 92.68% in the dimensions evaluated. The proposed telehealth model proved to be viable, especially in the context of social isolation.
Keywords: autism; parental guidance; telehealth; behavioral intervention